Design and Construction of Peanut Peeling Machine with a Capacity of 100 kg/hour - Rando Wijaya Sidauruk; Tambos August Sianturi; Winfronstein Naibaho; Jhon Supriadi Purba; Saloom Hilton Siahaan (International Journal of Technology and Education Research, 2026)
This research aim For make Design and Construction Machine Peanut Skin Peeler as well Capacity 100 kg/hour. Based on the results of the peanut roasting and peeling experiments, it can be concluded that the roasting time affects the final weight of the peanuts, the peeling results, and the quality of the peanut seeds produced. and a roasting time of 10 minutes by a sand temperature of 30 °C, the weight of the peanuts decreased from 1 kg to 0.95 kg. After peeling, the weight of the peanut seeds was 0.60 kg and the weight of the peanut shell was 0.35 kg. The percentage of unbroken peanuts reached 97%, while only 3% were broken. After roasting for 20 minutes, the final peanut weight decreased to 0.90 kg. The peeling results proved that the weight of the seeds was 0.57 kg and the weight of the shell was 0.33 kg. The percentage of whole peanuts decreased to 80%, while the percentage of broken peanuts increased to 20%. The experimental results also proved that the capacity of the peanut peeling machine reached 100 kg/hour by both experiments. Longer hulling times reduce the moisture content and weight of the beans, but increase the level of damage during hulling. Therefore, a hulling time of 10 minutes at 30°C yields the best results, producing more accurate hulling of the beans and reducing the level of damage